Validation and Transadaptation of Tinnitus Primary Function Questionnaire Into Central Kurdish Version (TPFQ-CK) - Hawramy, Mohammed Subhan Mohammed; Zmnako, Sherko Saeed F; Baban, Muaid Ismaiel Aziz (Journal of audiology & otology, 2024)
Tinnitus affects individuals' quality of life, and multiple surveys have been conducted to assess this effect. One questionnaire used is the Tinnitus Primary Function Questionnaire. The aim of this study was to assess the reliability and validity of the Central Kurdish version of the Tinnitus Primary Function Questionnaire (TPFQ-CK). We obtained permission from the originator of the TPFQ to proceed with this study. The English version was translated into Central Kurdish, following guidelines for the cross-cultural adaptation of health-related quality-of-life measures. A total of 205 participants who self-reported having subjective tinnitus for more than 3 months were included in this study. The TPFQ-CK and Tinnitus Handicap Questionnaire (THQ) were administered to all participants. Additionally, pure-tone audiometry was conducted. Internal consistency of the TPFQ-CK was reflected in the total score (Cronbach's alpha=0.933), and excellent consistency was present in test-retest reliability (intraclass correlation coefficient=1.000). The concordance correlation coefficient (concordance correlation coefficient=0.999) of the total TPFQ-CK score revealed high concordance and correlation between the two evaluations. The good construct validity of the TPFQ-CK was evidenced by the strong correlation (r=0.895) between the TPFQ-CK and THQ scores. The TPFQ-CK is a valid and reliable assessment tool for evaluating the influence of tinnitus on the quality of life of Central Kurdish speakers with tinnitus.